2009
DOI: 10.1111/j.1442-200x.2008.02733.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transfusion on the venous blood lactate level in very low‐birthweight infants

Abstract: Venous blood lactate measurements may offer some additional information regarding the optimal time for performing a transfusion. To the authors' knowledge this is the first report to study the changes in lactate levels using venous blood sampling in red blood cell transfusion in very low-birthweight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Serum lactate is an end product of strained anaerobic cellular metabolism and is elevated in tissue hypoxia, hypoperfusion, or injury. Serum lactate has been tested by few researchers as a marker of tissue perfusion and its usefulness as a biochemical trigger for transfusion in newborn infants32‐35 (Table ).…”
Section: Established Methods To Assess the Need For Blood Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum lactate is an end product of strained anaerobic cellular metabolism and is elevated in tissue hypoxia, hypoperfusion, or injury. Serum lactate has been tested by few researchers as a marker of tissue perfusion and its usefulness as a biochemical trigger for transfusion in newborn infants32‐35 (Table ).…”
Section: Established Methods To Assess the Need For Blood Transfusionmentioning
confidence: 99%
“…It has been demonstrated that pretransfusion serum lactate level decreases significantly after RBC transfusion 34‐36. In a randomized study of 16 preterm infants Ross and colleagues demonstrated that blood lactate may be useful to identify preterm infants who will benefit from RBC transfusion.…”
Section: Established Methods To Assess the Need For Blood Transfusionmentioning
confidence: 99%
“…The cut-off value for blood lactate (>1.8 mmol/L) was based on the reference range from the local laboratory. Lactate was used in the past as a marker of an oxygen deficit, helping in the optimal timing of RBC transfusion [ 20 ]. Lactate was used as a physiologic transfusion trigger due to limited number of patients in whom ScvO 2 could be determined.…”
Section: Methodsmentioning
confidence: 99%
“…Одним из них является метод определения тканевой оксигенации с помощью NIRS. Данный метод позволяет оценить различия между показателями церебральной и периферической оксигенации [17,25]. В ряде исследований описано улучшение показателей тканевой оксигенации, определенных с помощью NIRS, после заместительной трансфузии ЭСК крови у недоношенных новорожденных [8,9,24,26].…”
Section: обсуждение результатов исследованияunclassified